Comparison of two different shapes of stylets for intubation with the McGrath MAC® video laryngoscope: a randomized controlled trial. Issue 10 (October 2020) - Lim, Hyunyoung; Cha, Yun-Byeong; Ryu, Kyoung-Ho; Lee, Sung Hyun; Cho, Eun-Ah
Objective: This study was performed to compare two different shapes of stylets, 60° and J-shaped stylets, for intubation using the McGrath MAC® video laryngoscope (MVL). Methods: Two hundred twenty-two patients undergoing surgery under general anesthesia were randomly allocated to Group J (n = 111) or Group 60° (n = 111) and intubated using the MVL with the stylet bent into the allocated shape. The time to intubation (TTI) and other intubating profiles were compared between the groups. Multivariate regression analysis was used to determine the relationship between factors related to difficult intubation and TTI. Results: The TTI was not different between the two groups. There were also no differences in the intubating profiles between the two groups. In both groups, the TTI was longer with a modified Mallampati score (mMS) of ≥3 and percentage of glottic opening (POGO) score of <50. In Group J, the TTI was longer with a body mass index (BMI) of ≥30 kg/m 2 . Conclusion: The TTI during tracheal intubation with the MVL was not different between the two groups. The TTI was longer with an mMS of ≥3 and POGO score of <50. In Group J, the TTI was longer with a BMI of ≥30 kg/m 2 .